Brahmin Left Versus Merchant Right: Changing Political Cleavages in 21 Western Democracies, 1948–2020 - Gethin, Amory; Martínez-Toledano, Clara; Piketty, Thomas (Quarterly Journal of Economics, 2021)
Abstract This article sheds new light on the long-run evolution of political cleavages in 21 Western democracies. We exploit a new database on the socioeconomic determinants of the vote, covering more than 300 elections held between 1948 and 2020. In the 1950s and 1960s, the vote for social democratic, socialist, and affiliated parties was associated with lower-educated and low-income voters. It has gradually become associated with higher-educated voters, giving rise in the 2010s to a disconnection between the effects of income and education on the vote: higher-educated voters now vote for the “left,” while high-income voters continue to vote for the “right.” This transition has been accelerated by the rise of green and anti-immigration movements, whose distinctive feature is to concentrate the votes of the higher-educated and lower-educated electorates. Combining our database with historical data on political parties’ programs, we provide evidence that the reversal of the education cleavage is strongly linked to the emergence of a new “sociocultural” axis of political conflict.